Bomolochus bramus n. sp. (Copepoda, Poecilostomatoida, Bomolochidae) from the pomfrets (Bramidae) off Taiwan, with a list of nominal species and key to valid species of Bomolochus von Nordmann, 1832 - Ho, Ju-Shey; Lin, Ching-Long (Zootaxa, 2009)
A new species of copepod, Bomolochus bramus n. sp. (Poecilostomatoida: Bomolochidae), is described from the gills of Brama japonica Hilgendorf and Eumegistus illustris Jordan & Jordan collected off the east coast of Taiwan. This is the first species of bomolochid copepod reported from the pomfrets (Bramidae). The new species is distinguished from its congeners by having a combination of the following characters: (1) a pair of rostral tines; (2) the fourth basal element on the antennule modified as a hook, about as long as its neighboring outer pilose setae; (3) two large patches of spinules on the ventral surface of the anal somite; (4) a large patch of spinules on the ventral surface of the caudal ramus; (5) armature formula of II, I, 5 on the terminal exopodal segment of legs 3 and 4; and (6) leg 4 endopod with a relatively short terminal segment ornamented with long setules along the outer margin and long spinules along the distal margin. In addition to the report of the above new species, a list of the nominal species of Bomolochus von Nordmann, 1832, including their current taxonomic status, is provided. A key to the valid species is also included.